Aquatic insect responses to predation and temperature: variation in context dependent trophic interactions - Morton, Scott Gregory, author; Poff, N. LeRoy, advisor; Kondratieff, Boris, committee member; Schmidt, Travis, committee member (Colorado State University. Libraries, 2017)
Trophic cascades, the indirect effects of carnivores on primary producers mediated by herbivores, remains a central theme of ecological theory. How climate change will alter the mechanisms controlling such interactions remains largely unexplored, certainly in stream ecosystems. In montane streams, stonefly predators have been documented to indirectly affect algal biomass by influencing the distribution, abundance, behavior, and life histories of invertebrate grazers. Density mediated indirect interactions (DMII) occur when primary producer biomass is primarily influenced by changes in herbivore abundance due to consumption by predators. Trait-mediated indirect interactions (TMII) alter primary producer abundance through non-consumptive interactions such as anti-predatory behaviors. In this research, I conducted mesocosm experiments on stonefly predators and mayfly prey to determine the relative importance of grazers on regulating algal production under three temperature treatments intended to simulate climate warming. Furthermore, I examined the influence of both DMII and TMII on algal production through consumptive and non-consumptive predatory treatments. I found algal biomass to decrease as temperature increased, however found no differences among grazer-alone treatments versus DMII or TMII on algal production.
Keywords: TMII; DMII; trophic cascades